1995
DOI: 10.1002/jlb.57.6.891
|View full text |Cite
|
Sign up to set email alerts
|

Processing of complex antigens and simple hapten-like molecules by epidermal Langerhans cells

Abstract: Langerhans cells (LCs) are antigen-presenting cells of the skin that trap small contact-sensitizing molecules and induce cutaneous hypersensitivity. LCs can present larger molecules but the mechanisms of processing have required investigation. A system combining in vitro culture of antigen with epidermal cells in the presence of inhibitors, followed by fixation and transfer of these antigen/drug-treated epidermal cells to naive mice, was developed to investigate the steps of antigen processing. Langerhans cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Cultured Langerhans cells, on the contrary, do not process efficiently but can present pre-processed proteins to T cells extremely well [l]. In general, antigen fragments are presented differently from the large epitopes [14]. It has, therefore, been postulated that Langerhans cells trap antigens in the epidermis and carry them to the draining lymph nodes where the corresponding polypeptide fragments are finally presented to T cells [l].…”
Section: Resultsmentioning
confidence: 99%
“…Cultured Langerhans cells, on the contrary, do not process efficiently but can present pre-processed proteins to T cells extremely well [l]. In general, antigen fragments are presented differently from the large epitopes [14]. It has, therefore, been postulated that Langerhans cells trap antigens in the epidermis and carry them to the draining lymph nodes where the corresponding polypeptide fragments are finally presented to T cells [l].…”
Section: Resultsmentioning
confidence: 99%
“…Efficient uptake of (protein) antigens, either through specific receptor-mediated endocytosis and/or (macro)pinocytosis might, therefore, be expected. Several studies have shown that freshly isolated murine LC endocytose protein antigens, and the high-affinity receptor for IgE (Fc 4 R1) has been implicated in the uptake of allergens by human epidermal LC [13,14,[27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that an active process, including perhaps internalization and processing, is required after TNP or FITC molecule binding. Internalization of membrane molecules has been shown after hapten treatment or hapten-carrier contact with murine Langerhans cells (Becker et al, 1995;Lempertz et al, 1996); however, if the need for processing is well established with hapten-carrier complexes (Ma et al, 1994;Woods et al, 1995), it remains controversial with hapten alone (Moulon et al, 1993).…”
Section: Discussionmentioning
confidence: 99%